Factors Influencing Successful Educational Management by using Electronic Supply Chain for Higher Education Institution in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim to study factors influencing successful educational management by using electronic supply chain for higher education institutions in Thailand.The research divide into three steps namely the studies and syntheses of related documents and to study about factors influencing successful educational management by in-depth Interview executives , Faculty of Home Economic Technology, Rajamangala University of Technology Krungthep ,including do an in-depth interview of ten experts in three areas, that is, five experts in supply chain, three experts in electronics and technology information, and two experts in curriculum. According to the research study we found that there were six factors successful educational management by using electronic supply chain for higher education institutions in Thailand namely supplied input for educational, Educational management in the university, finished product from university, customers benefit from university, the main activities of educational in supply chain and electronic supporting system. All factors will lead to the development of educational using electronic supply chain for higher education institutions in Thailand.